Factors Influencing E-Wallet Usage Among Generations X and Y - Agustin, Isnaini Nuzula; Oskar, Franky; Suprapto, Yandi (Manunggal Halim Jaya, 2026)
Digital transformation has changed people's preferences in transactions, especially in choosing e-wallet-based payment methods. Although the growth potential of e-wallets in Indonesia is quite large, the adoption rate remains below expectations among Generation X and Y, who have greater purchasing power compared to Generation Z. While younger users tend to adopt e-wallets more easily, older generations still show inconsistent usage behavior, indicating that achieving sustainable adoption remains a challenge. This study aims to analyze the factors that influence continuance intention in the use of e-wallet services among Generations X and Y in Batam City. A total of 155 respondents from both generations were involved through the distribution of online questionnaires. The sampling technique used was non-probability sampling with a purposive sampling approach. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the help of the SmartPLS application. The results of this study indicate that perceived security and utilitarian value significantly influence continuance intention. Meanwhile, utilitarian value and continuance intention significantly influence e-wallet usage. Additionally, continuance intention is proven to mediate the relationship between perceived security and e-wallet usage. Generation X users tend to prioritize security and personal data protection when deciding to continue using e-wallets, whereas Generation Y users focus more on convenience and functional benefits. Therefore, these findings are expected to contribute to e-wallet service providers and policymakers in designing strategies to address these generational differences to strengthen long-term adoption.